Number in Nivkh - Gruzdeva, Ekaterina (2023)
The chapter discusses the expression of number in Nivkh (isolate), which is spoken in the Far East of Russia. Typologically, Nivkh is a (poly)synthetic language with a rather complex (morpho)phonology and predominant suffixation. In Nivkh, number distinctions relate both to the count of participants, which is expressed by numerals and personal pronouns, as well as through nominal and verbal inflection, and to the count of events, which is determined at the clausal level, so that plurality of events is marked either by reduplication of nominal and verbal stems or by verbal suffixation. A maximum number of number features (singular vs. dual vs. plural) is attested in the personal pronouns and the hortative verb forms, whereas in all other forms a two-way number contrast between singular and plural is observed. The system of numerals contains at least thirty-three suffixalized classifiers. As an inflectional category, number is not obligatory either for nouns or for verbs. Those finite verb forms and converbs that can be conjugated display various patterns of verbal agreement. This can best be explained by assuming that the verbal forms are the results of morphosyntactic restructuring at different time levels. Peer reviewed